If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -3 + -7x + 8 = 11(-1 + -5x) + -4(-4 + 6x) Reorder the terms: -3 + 8 + 12x + -7x = 11(-1 + -5x) + -4(-4 + 6x) Combine like terms: -3 + 8 = 5 5 + 12x + -7x = 11(-1 + -5x) + -4(-4 + 6x) Combine like terms: 12x + -7x = 5x 5 + 5x = 11(-1 + -5x) + -4(-4 + 6x) 5 + 5x = (-1 * 11 + -5x * 11) + -4(-4 + 6x) 5 + 5x = (-11 + -55x) + -4(-4 + 6x) 5 + 5x = -11 + -55x + (-4 * -4 + 6x * -4) 5 + 5x = -11 + -55x + (16 + -24x) Reorder the terms: 5 + 5x = -11 + 16 + -55x + -24x Combine like terms: -11 + 16 = 5 5 + 5x = 5 + -55x + -24x Combine like terms: -55x + -24x = -79x 5 + 5x = 5 + -79x Add '-5' to each side of the equation. 5 + -5 + 5x = 5 + -5 + -79x Combine like terms: 5 + -5 = 0 0 + 5x = 5 + -5 + -79x 5x = 5 + -5 + -79x Combine like terms: 5 + -5 = 0 5x = 0 + -79x 5x = -79x Solving 5x = -79x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '79x' to each side of the equation. 5x + 79x = -79x + 79x Combine like terms: 5x + 79x = 84x 84x = -79x + 79x Combine like terms: -79x + 79x = 0 84x = 0 Divide each side by '84'. x = 0 Simplifying x = 0
| 1=5(t-6) | | -x-54=-7x+54 | | X+2+x+2+x+2+X+2=12 | | 1+x+4+x+7+x+10=0 | | 0.02(n-550)=105 | | 4p+3q=41 | | 12.6x=56.7 | | 6n=3n-2+2(2n+1) | | -6s-11=-2s+5 | | 9k-26=6k | | 2x+7-26=17-4x+5 | | 2xy+60-5xy=x+10+y | | -2p-6=10-10p | | 26+2x=263 | | x-32=63-4x | | 0=-X^2-6X | | 6x+8=46 | | 12x^2y+8xy+4xy^2= | | 5x+16=8x-8 | | 5x-306=20 | | 18+x=x+11+12 | | 2xy-x+40-y=5y-20+xy | | T=141.68+.75M | | -7+4m=6n-5 | | 37xsquared+35x-14= | | .2x-25=18 | | -38+3x=38-x | | 4x^2+15x-4=f(x) | | ryan=rike | | 38+(7x+1)+(10x+22)=180 | | 10b^2+7=397 | | 8(x-3)-(6-2x)=2(x-2)-5(5-x) |